The Study of the Relationship between Marketing Factors and Customer’s Decision to Purchase of Point of Sale Systems (Pos) of Casual Dining Restaurant in Bangkok, Thailand - Waraporn Wongsapun วราภรณ์ วงษาพันธ์; Dolly Samson ดอลลี่ แซมซัน (Dusit Thani College Journal, 2018)
The objectives of this research were consideration of relationship between marketing factors and customer’s decision to purchase the POS systems for casual dining restaurant and this research aimed to indentify marketing factors on important, which were related to purchase decision of the customers for casual dining restaurant. It reports on research conducted in March-April 2016. As the result indicated to marketing factors as the products, price and people, which are influencing to decision marker attended to buy POS systems using for restaurant business. Research Methodology; This research is quantitative method by the researcher collected data with questionnaire survey of the 100 respondents by qualified respondent of position which the owners, restaurant manager, operation manager and others which base on theirs responsible take decision making for business. Research findings : For the marketing factors (7P’s) that important to decision maker consider to purchase POS systems is the Product, mostly respondents take important extremely at mean = 4.56 which must be fits with the restaurant concept. Next to Price which results stand on = 4.54, for price must to appropriate with product which each of provider differ based on its software, hardware and application. The decision maker will examine what they needs. People also to extremely important in level = 4.50, which respondents take important to professionalism. It is important to have a clear of problem resolution and customer support of their problem as well as training, which effected to creditable to customer’s perception.